On the formation of identity: Fact and fictions: Walkerdine V (1990) Schoolgirl fictions. London: Verso. - Callaghan, Jane E. M. (PINS-Psychology in Society, 2026)
Using a combination of theoretical pieces about the production of masculinity and femininity, and intensely personal reflections, Valerie Walkerdine tells her Schoolgirl fictions. The book reads as an intellectual autobiography and a collection of ten years of her academic writings. She looks at the formation of identity - how gender and class come to be lived as real, distinct categories. She argues that in fact they are "fictions", created in and suffused with fantasy. She describes how these fictions are produced and inscribed in regulative social practices, using the school system as her primary example. At the same time she presents the way in which she herself has lived out these fictions.